2021
DOI: 10.1214/20-aoas1395
|View full text |Cite
|
Sign up to set email alerts
|

The role of scale in the estimation of cell-type proportions

Abstract: Complex tissues are composed of a large number of different types of cells, each involved in a multitude of biological processes. Consequently, an important component to understanding such processes is understanding the cell-type composition of the tissues. Estimating cell type composition using high-throughput gene expression data is known as cell-type deconvolution. In this paper, we first summarize the extensive deconvolution literature by identifying a common regression-like approach to deconvolution. We c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…To test the performance of different approaches to computational deconvolution of RNA-seq data (Table 1), six deconvolution methods (DWLS, Bisque, MuSiC, BayesPrism, CIBERSORTx, and hspe) were run on this DLPFC dataset of 110 bulk/fractionated RNA-seq samples [5][6][7][8][9]11] to estimate proportions of seven broad cell types. The reference snRNA-seq dataset was subset to the Mean Ratio top25 cell type marker genes for deconvolution.…”
Section: Benchmark Of Selected Deconvolution Methods With Mean Ratio ...mentioning
confidence: 99%
See 2 more Smart Citations
“…To test the performance of different approaches to computational deconvolution of RNA-seq data (Table 1), six deconvolution methods (DWLS, Bisque, MuSiC, BayesPrism, CIBERSORTx, and hspe) were run on this DLPFC dataset of 110 bulk/fractionated RNA-seq samples [5][6][7][8][9]11] to estimate proportions of seven broad cell types. The reference snRNA-seq dataset was subset to the Mean Ratio top25 cell type marker genes for deconvolution.…”
Section: Benchmark Of Selected Deconvolution Methods With Mean Ratio ...mentioning
confidence: 99%
“…Increasing numbers of bulk RNA-sequencing (RNA-seq) and single cell or nucleus RNA-seq (sc/snRNA-seq) datasets have been generated, sometimes uniformly processed, and publicly shared [1][2][3][4]. RNA-seq data historically has been cheaper to generate than sc/snRNA-seq data, leading to a surge in methods that perform cellular deconvolution and estimation of cell type proportions using reference sc/snRNA-seq data [5][6][7][8][9][10][11]. Some methods can use these estimated cell type proportions to deconvolve cell type specific gene expression [12][13][14] to overcome cellular heterogeneity and identify nuanced gene expression signals that would otherwise be masked in bulk RNA-seq data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several issues with the linear framework have been identified [ 30 ]. More recently, the authors of [ 36 ] showed problems associated with different scales of gene expression within the linear framework and then proposed the following hybrid model: where accounts for systemic technical variation. Equivalently, …”
Section: Methodsmentioning
confidence: 99%
“…The role of marker genes in deconvolution remains particularly unclear: a recent benchmark suggests iScience Article that the quality of markers is more important than the deconvolution method (Avila Cobos et al, 2020), and in most studies the influence of the number of markers is only partially assessed (Newman et al, 2019;Hunt and Gagnon-Bartsch 2021). Our annotation assessment suggested that cell types are best captured with 10-200 meta-analytic markers; deconvolution is a natural place to test this heuristic.…”
Section: Meta-markers Improve Deconvolution Performancementioning
confidence: 96%